2010
DOI: 10.5194/acp-10-3385-2010
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of tracer transport to model resolution, prescribed meteorology and tracer lifetime in the general circulation model ECHAM5

Abstract: Abstract. Atmospheric transport of traces gases and aerosols plays an important role in the distribution of air pollutants and radiatively active compounds. For model simulations of chemistry-climate interactions it is important to know how the transport of tracers depends on the geographical resolution of the general circulation model. However, this aspect has been scarcely investigated until now. Here, we analyse tracer transport in the ECHAM5 general circulation model using 6 independent idealized tracers w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…The horizontal diffusion in the results from the T21L19 is probably overestimated smearing out the 10 Be gradients in the mid-and low latitudes. This is in agreement with previous findings by Aghedo et al (2010) who found weaker meridional transport at coarse resolutions, allowing for more diffusion towards low latitudes. Figure 11 shows the stratospheric 10 Be divided into the 30-degree bands.…”
Section: Mixing and Transport Path Of 10 Besupporting
confidence: 83%
See 3 more Smart Citations
“…The horizontal diffusion in the results from the T21L19 is probably overestimated smearing out the 10 Be gradients in the mid-and low latitudes. This is in agreement with previous findings by Aghedo et al (2010) who found weaker meridional transport at coarse resolutions, allowing for more diffusion towards low latitudes. Figure 11 shows the stratospheric 10 Be divided into the 30-degree bands.…”
Section: Mixing and Transport Path Of 10 Besupporting
confidence: 83%
“…The five bars at each latitude band show the model resolutions "T63L47", "T42L39", "T42L31", "T21L19" as well as the "T42L39old", published in Heikkilä et al (2009), respectively. ECHAM5 model has been reported by Aghedo et al (2010) who found that meridional transport was decreased at coarse resolution, leading to increased concentrations of surface tracers in the tropics.…”
Section: Mixing and Transport Path Of 10 Bementioning
confidence: 99%
See 2 more Smart Citations
“…However, tracer transport in global chemistry-climate models can also be sensitive to many other aspects of the model that are beyond the scope of this study, such as model resolution, the use of prescribed meteorology to nudge the chemistry climate model towards the observed atmospheric state (Aghedo et al, 2010), numerical formulations of atmospheric dynamics (Rasch et al, 2006), and the formulation of the parameterization of deep convective transport (Mahowald et al, 1995;Luo et al, 2003;Tost et al, 2006b;Lawrence and Salzmann, 2008). The sensitivity of modelled transport to particle characteristics as simulated here could potentially change if these or other aspects of the model were changed.…”
Section: Discussionmentioning
confidence: 99%